Toxin‐Blocking Textiles: Rapid, Benign, Roll‐to‐Roll Production of Robust MOF‐Fabric Composites for Organophosphate Separation and Hydrolysis. Issue 2 (18th November 2022) - Morgan, Sarah E.; Willis, Morgan L.; Dianat, Golnaz; Peterson, Gregory W.; Mahle, John J.; Parsons, Gregory N.
Abstract: Current approaches to create zirconium‐based metal–organic framework (MOF) fabric composites for catalysis, water purification, wound healing, gas sorption, and other applications often rely on toxic solvents, long reaction/post processing times, and batch methods hindering process scalability. Here, a novel mechanism was reported for rapid UiO‐66‐NH2 synthesis in common low‐boiling‐point solvents (water, ethanol, and acetic acid) and revealed acid–base chemistry promoting full linker dissolution and vapor‐based crystallization. The mechanism enabled scalable roll‐to‐roll production of mechanically resilient UiO‐66‐NH2 fabrics with superior chemical protective capability. Solvent choice and segregated spray delivery of organic linker and metal salt MOF precursor solutions allowed for rapid MOF nucleation on the fiber surface and decreased the energy and time needed for post‐processing, producing an activated composite in less than 165 min, far outpacing conventional MOF‐fabric synthesis approaches. The MOF‐fabric hydrolyzed and blocked permeation of the chemical warfare agent soman, outperforming the protection‐standard activated carbon cloth. This work presents both chemical insights into Zr‐MOF powder and fabric composite formation by a rapid, industrially relevant approach and demonstrates its practicality and affordability for high‐performing personal protective equipment. Abstract : MOFs against toxins : A scalable, rapid metal–organic framework (MOF)‐fabric production method is developed using benign solvents. The MOF‐composites are tested for lethal organophosphate neutralization and permeation for application to chemical warfare agent protective equipment.